Peran Masyarakat dan Pesantren dalam Implementasi Adaptasi dan Mitigasi Perubahan Iklim sebagai Upaya Pelaksanaan Program Kampung Iklim di Desa Plumpang Kabupaten Tuban - Lestari, Dwi Puji; Falasifah, Nihlatul; Zakariya, A. Fahmi (Journal of Community Development and Disaster Management, 2024)
The purpose of this study is to determine how Islamic boarding schools and communities in Plumpang Village, Tuban Regency, are using adaptation and mitigation strategies for climate change. A nationwide program called the Climate Village Program (ProKlim) aims to lower greenhouse gas emissions and make communities more resilient to the effects of climate change. The descriptive qualitative method was employed in this study, and interviews, observations, focus groups (FGDs), and documentation were used to gather data. The findings demonstrated that the Plumpang Village community has undertaken a number of adaptation initiatives, including the building of reservoirs, biopores, and water management infrastructure. Additionally, using yard space, using renewable energy sources, and practicing sustainable waste management are all part of mitigation efforts. The examination of the effectiveness of adaptation and mitigation produced a final ProKlim value of 52.72%, with a percentage of adaptation value of 19.07% and mitigation value of 15.20%. This study demonstrates that, given the complexity of climate change, it is imperative to integrate mitigation and adaptation strategies. For the next generation's living conditions and wellbeing to improve, there needs to be strong global policy advocacy coupled with interdisciplinary collaboration across government agencies, the business sector, and communities. The program also aims to support locally run eco-friendly businesses, which should strengthen community resistance to the negative effects of climate change.